IMPLEMENTASI PROGRAM REDUCE, REUSE RECYCLE (3R) BANK SAMPAH PERMATA BUNDA DALAM PENGELOLAAN SAMPAH DI LINGKUNGAN SEKOLAH MENENGAH ATAS KECAMATAN PANGKALAN KERINCI - Badriya Hazam; Zulfan Saam; Suardi Tarumun (Program Pascasarjana Universitas Riau, 2020)
The implementation of waste management through the Reduce, Reuse Recycle (3R) Waste Bank Permata Bunda Program were evaluated the study aimed at : (1) are describe process and results of the Implementation of Waste Management through the 3R Program. (2) Examining the feasibility of implementation of waste management. (3) testing the effectiveness process of implementation of waste management. The 3R Permata Bunda's programme through (1) Reuse means reusing waste that can still be used for the same function or other functions. (2) Reduce means reducing everything that results in waste. (3) Recycle means to recycle waste into useful new products or products.The data in this study are in the form of a score assessment of the implementation of waste management from respondents through questionnaires. The respondents consisted of 40 students from SMAN 1 Pangkalan Kerinci and SMAN 2 Pangkalan Kerinci, and 4 experts or managers. The Implementation of Waste Management Through the 3R program of Permata Bunda Waste Bank evaluated from (1) The physical appearance (2) Practical use (3) Effectiveness of the process. The result showed that Implementation of Waste Management Through the 3R program of Permata Bunda Garbage Bank of Pangkalan Kerinci is categorized as feasible, practical, and effectively applied in Pangkalan Kerinci District